1982
DOI: 10.1002/ijc.2910290213
|View full text |Cite
|
Sign up to set email alerts
|

Syngeneic and allogeneic cell‐mediated cytotoxicity against marek's disease lymphoblastoid tumor cell lines

Abstract: Cell-mediated cytotoxicity (CMC) of lymphocytes obtained from chickens infected with Marek's disease (MD) virus against allogeneic MD lymphoblastoid cell lines has been reported by several research groups. Recently, we established a number of cell lines from MD tumors obtained from highly inbred chickens and characterized for major and minor histocompatibility antigens. Allogeneic versus syngeneic CMC was studied using those cell lines and lymphocytes obtained from chickens 6-8 days post infection with SB-1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We showed that CD8 was down-regulated at the transcriptional level during MDV infection (Figs 3 and 4). It is well known that MDV can cause a functional deficiency of CTL, for example delayed rejection of Rous sarcomas or MD transplantable tumour cells (Calnek et al, 1975), increased susceptibility to coccidiosis (Biggs et al, 1968) and absence of specific cytotoxic activities against MD tumour cells (Schat et al, 1982;Powell et al, 1983). Down-regulation of CD8, therefore, may be important for the immunosuppression of T cells.…”
Section: T Morimura and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that CD8 was down-regulated at the transcriptional level during MDV infection (Figs 3 and 4). It is well known that MDV can cause a functional deficiency of CTL, for example delayed rejection of Rous sarcomas or MD transplantable tumour cells (Calnek et al, 1975), increased susceptibility to coccidiosis (Biggs et al, 1968) and absence of specific cytotoxic activities against MD tumour cells (Schat et al, 1982;Powell et al, 1983). Down-regulation of CD8, therefore, may be important for the immunosuppression of T cells.…”
Section: T Morimura and Othersmentioning
confidence: 99%
“…At the same time, MDV causes secondary immunosuppression, which is characterized by unresponsiveness to mitogen stimulation (Theis et al, 1975), delayed rejection of Rous sarcomas or MD transplantable tumour cells (Calnek et al, 1975), and increased susceptibility to coccidiosis (Biggs et al, 1968). Interestingly, cytotoxic T lymphocytes (CTL) against syngenic MD tumour cell lines, which had been thought to be important for tumour inhibition, were not detected in chickens infected with MDV (Schat et al, 1982). Subsequently, MDV can cause the development of CD4 + T cell lymphoma in chickens (Schat et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although CD4-/CD8-T-cells have not yet been described in chickens, the author's group has CU14 (B 19 B 19 ) in a 4-h assay, CU36 (B 17 * 17 ) in a 4-h assay; and CU36 in a 8-h assay, respectively. From: Schat et al (1982). Reproduced with permission.…”
Section: Table 2 Detection Of Marek's Disease Tumor-associated Antigmentioning
confidence: 96%
“…This recombinant fowlpox virus induces both humoral and cellular immunity via CD8 + T cells immediately after the vaccination, indicating that immune responses against gB might be essential for the protective effects induced by the vaccines. Interestingly, a series of MD vaccines can induce specific cytotoxicity of lymphocytes against MHC-restricted allogenic but not syngenic tumor cell lines [71].…”
Section: The Significance Of Cd8 + T Cells In the Protective Effects mentioning
confidence: 99%